HOW TO IDENTIFY VIEWER SPENDING INTENTION AND HAPPINESS IN LIVESTREAMING: VIEWERS' PERSPECTIVE ON CONTENT CREATORS - Arnanda Primadana, Ligasyah
Recently, livestreaming has emerged as a widely embraced method of generating digital material, with specific individuals referred to as livestreamers attaining substantial fame and exerting significant influence. There are big gaps in live streaming by content creator researchers in journals. To fill that gap, researchers tried to create live-streaming research with viewers' perspectives as the central aspect of the topics. The research uses mixed methods to get the answer to the research question. The first stage of the research was doing some literature review to get basic questions for the explorative study; after the explorative study finished, the output included variables possible into the study. The definition of these variables is a basis for creating the questionnaire as an adaptation questionnaire from past literature. The next step is quantitative research with analysis using PLS-SEM with the application Smart PLS 3. The last step is analyzing the data to create the findings while combining qualitative and quantitative results for better results and implications. For the qualitative study, our research involved 19 participants. For quantitative research, the data totals 514 participants.